Effectiveness of Bee Pollen on Recovery of Submaximal Exercise Pulse Rate - Sitinjak, Rico Wanda (STKIP PGRI Jombang, 2023)
Exercise is an activity that is carried out systematically, and has been programmed, cyclical, regular and carried out several times using the capacity given progressively and has the aim of preparing itself in the development of individual quality to achieve certain goals. Pulse rate is an indicator that is needed by a person to know and carry out physical exercise properly. Energy is needed during physical exercise to move muscles and organs. To support the acceleration of recovery Bee Pollen contains antioxidant compounds useful for accelerating recovery back to normal. The method used is a quantitative method with the type of research Quasi Experiment. The research design is using a pre-posttest control group design. From the results of the study, it is proven that the research hypothesis (H0) will be returned and (Ha) is recognized or it can be interpreted that there is a significant difference between two or more groups or the average condition of pulse rate reduction over time. It has been proven that there is a significant difference in supplementing Bee Pollen from both experimental and control groups for pulse rate recovery after submaximal exercise. so that the experimental group has a better recovery process compared to the control. This study shows that there is a significant effect of supplementing Bee Pollen in the experimental group on pulse rate after submaximal exercise and there is a significant difference in the effects of both experimental and control groups on heart rate after submaximal exercise.